Made up how the beauty industry manipulates consumers, preys on women's insecurities, and promotes unattainable beauty standards - Laham, Martha (Rowman & Littlefield, 2020)
"Made Up: How the Beauty Industry Manipulates Consumers, Preys on Women's Insecurities, and Promotes Unattainable Beauty Standards takes a hard look at the multibillion-dollar beauty industry, which promotes unrealistic beauty standards, perpetuates gender stereotypes, and uses sexual objectification to sell products. The book is divided into four parts. Part 1 explores the global beauty industry, traces the cultural history of cosmetics, examines the regulatory climate of the cosmetics industry, and profiles the beauty consumer. Part 2 investigates the pervasiveness and persistence of the feminine beauty ideal, explores the globalization of Western standards of beauty, analyzes the myth-making power of beauty advertising, and decodes archetypal and stereotypical portrayals of women in beauty ads. Part 3 investigates the decorative and sexual depictions of women in beauty advertising and analyzes the power of celebrity beauty endorsements. Part 4 looks at the interplay between images of physical perfection in advertising messages and the surge in body modification and enhancement"--